English Reading Strategy Use by University Students in Vietnam = Nghiên cứu chiến lược đọc tiếng Anh của sinh viên Đại học ở Việt Nam. Degree of doctor of Linguistics: 91401 - Nguyễn, Thị Bích Thủy (2019)
The present study investigated the strategy use by Vietnamese university students when they read general English materials. It also examined if there were differences in the use of reading strategies between students who learned English as a compulsory subject at university (EFL students) and those who used English as a medium of instruction in the university (EMI students).